Temporal and Spatial Changes in Soil Quality at Shooting Ranges: A Case Study in Croatia - Željka Zgorelec; Nikica Šprem; Radovan Abramović; Marija Galić; Iva Hrelja; Domina Delač; Toni Safner; Ivica Kisić (Land)
In this study, the effect of ammunition on soil quality (physical and chemical indicators) at shooting ranges was investigated at four sites in Croatia. The sites differ in soil type (fluvisols, leptosols and terra rossa) and climatic conditions (Mediterranean and continental). The intensity of shooting range use (calculated from the age of the lane and the average number of targets used per year) and the distance from the shooting range (−40 m to +240 m) were examined in relation to soil chemical composition and soil quality. High contents of Pb and Sb at 100 m from the shooting position were observed in fluvisol and terra rossa soils, and the contamination factors (CFs) ranged from 6 up to 97. The study found high natural soil Cr and Ni content in leptosols and terra rossa due to paedogenic reasons (CFs < 1.3) and soil acidification (a decrease in soil pHKCl) due to ammunition/target use. Long-term measures for sustainable soil management and environment protection must be taken at shooting ranges to minimise the potential risks to ecosystems, wildlife and human health (an EU strategy).